2019
DOI: 10.1002/jor.24328
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Mouse Anterior Cruciate Ligament‐Complex Changes Following Exercise During Pubertal Growth

Abstract: Postnatal development and the physiological loading response of the anterior cruciate ligament (ACL) complex (ACL proper, entheses, and bony morphology) is not well understood. We tested whether the ACL-complex of two inbred mouse strains that collectively encompass the musculoskeletal variation observed in humans would demonstrate significant morphological differences following voluntary cage-wheel running during puberty compared with normal cage activity controls. Female A/J and C57BL/6J (B6) 6-week-old mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Furthermore, most bony morphological features are considered to be innate shapes that do not change. However, data exist showing that repeated loading from training and sport or after ACL reconstruction can cause bone remodeling 39–42 . In the future, bony morphological differences will be analyzed between athletes in different types of sports.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most bony morphological features are considered to be innate shapes that do not change. However, data exist showing that repeated loading from training and sport or after ACL reconstruction can cause bone remodeling 39–42 . In the future, bony morphological differences will be analyzed between athletes in different types of sports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the group of weight lifters with hypertrophied ACLs potentially due to their training through puberty, 17 exercise through periods of growth has also been shown to increase the ACL size and improve its mechanical properties in animal models. 6,36,42 Therefore, the potential for the ACL to be ''trained,'' so to speak, to become larger, more robust, and thus less at risk of injuries is apparent, but many critical questions remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in ACL strength (ie, greater energy at ligament failure) and stiffness have been reported in growing rats and rabbits. 6,42 Also, most recently, Schlecht et al 36 revealed that exercise during puberty significantly increased the ACL CSA in a mouse model. Evidence of hypertrophied ACLs also exists for the human ACL.…”
mentioning
confidence: 98%
See 2 more Smart Citations